Perancangan Interior Masterchef Junior School di Surabaya - Chellia Laurentia Djimantoro (Intra, 2017)
A culinar facility in Surabaya growing rapidly along with the many new cafes and restaurants in town. The culinary world itself can’t be separated from the cooking activities, and at this time not only adults are able to create delicious dishes, but the children also have started to love cooking and start to learn to cook by looking from their daily activities of parents, chefs in the restaurant, and also the television cooking program that is MasterChef Junior which is a cooking competition, but educational facilities for cooking for the children themselves are still less accommodating in Surabaya. Therefore the design of this cooking school aims to accommodate culinary educational facilities for all children who have a hobby in cooking, including children who are disabled because there is still little facilities that accommodate those needs. Brand from Masterchef Junior itself which is well known to many people it is very unfortunate if only provide the only competition facility, therefore the design of this time is a new proposal for the Masterchef Junior to provide educational facilities for children (normal and disabled) has complete facilities both from theory room, demo room, culinary and bakery laboratories, and other supporting facilities such as mini library, restaurant, urban gardening, mini market for the public so that people are interested in entering into and with the concept of Livable in Diversity creating a comfortable cooking school facility in spite of the difference of users (normal and disabled) in 3 aspects: ergonomics, sustainable, and safety.